2012
DOI: 10.1177/0040517512450765
|View full text |Cite
|
Sign up to set email alerts
|

Plasma modification of Kevlar fabrics for ballistic applications

Abstract: The currently used high-performance fiber materials for soft body armor have very low surface friction and this has become an issue in the effectiveness of ballistic energy absorption. In this study, non-polymerizing reactive plasma gas N2 and chemical vapor (CH3)2Cl2Si were employed to modify Kevlar fabric surface for the application of ballistic impact material. Scanning electron microscopy observations yield information about the surface effect of the fabrics after plasma treatment. The surface morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 9 publications
(5 reference statements)
0
45
0
Order By: Relevance
“…In other words, the sizes of samples in previous simulation work are smaller than those in actual ballistic impact experiment [4][5][6][7][8][9][10][11][14][15][16] . Cunniff [18] applied a sample holder with three sizes of apertures to clamp a single-layer fabric.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…In other words, the sizes of samples in previous simulation work are smaller than those in actual ballistic impact experiment [4][5][6][7][8][9][10][11][14][15][16] . Cunniff [18] applied a sample holder with three sizes of apertures to clamp a single-layer fabric.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Given the complexity of hierarchical structure of ballistic fabrics, the influence factors from the structure are considerable [1] , for instance, the strength, the pattern, the warp and weft yarn density and so on. Among those numerous influence factors, the inter-yarn friction is outstanding and vital and its effects on the ballistic performance have been investigated by some researchers, such as Hearle et al [2] , Briscoe and Motamedi [3] , Duan et al [4,5] , Zeng et al [6] , Rao et al [7] , and Sun et al [8] , Minh et al [9] , Gogineni et al [10] , Nilakantan et al [11] .,Sun et al [12,13] , Zhou et al [14] ,Wang et al [15] and Daset al [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Such yarns have been used in making ballistic fabrics. Sun and Chen (2012) reported that a rough surface has been observed on the N 2 and (CH 3 ) 2 Cl 2 Si plasma-treated Kevlar® fibre surface. A yarn pulling out test result showed an 18% and 300% increase in pulling out a yarn from the two types of plasmatreated fabric, respectively, in comparison to that of the untreated fabric.…”
Section: Surface Modification Of Ballistic Materialsmentioning
confidence: 98%
“…Numerical method is one of the commonly used methods for ballistic investigation [5][6][7][8][9][10][11][12][13][14] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…With this method, Zeng et al [7] , Gogineni et al [8] , , Zhou et al [10] and Sun et al [11] in their simulations observed that the energy absorption increases with the coefficient of friction in certain range ,whereas the energy absorption begins to decrease at much higher frictional levels. Rao et al [13] and Parsons et al [14] found that the ballistic limit is also affected by inter-yarn friction.…”
Section: Accepted Manuscriptmentioning
confidence: 99%